Market Reaction to Rights Issue Announcement: An Event Study on Conventional Banks in Indonesia - Risa Ramadhianti; Helma Malini; Wenny Pebrianti; Wendy; Anggraini Syahputri (Journal of Educational Management Research, 2026)
This study aims to examine market reactions to rights issue announcements among conventional banking companies by assessing changes in abnormal returns, trading volume activity, and stock return volatility before and after the announcements. A quantitative event study design was employed using secondary data from 26 conventional banking issuers that announced rights issues during 2020–2024. An 11-trading-day event window, covering five days before and five days after the announcement date, was applied. Market reactions were measured using abnormal return, trading volume activity, and stock return volatility. Because the data did not satisfy the normality assumption, the Wilcoxon Signed-Rank Test was used to examine differences between the pre- and post-announcement periods. The findings indicate significant differences in abnormal return, trading volume activity, and stock return volatility following rights issue announcements. The results demonstrate that rights issue information generates measurable changes in investor responses, reflected in changes in returns, trading intensity, and stock price fluctuations. The findings provide practical insights for investors in evaluating rights issue announcements as relevant information for investment decisions. The study also contributes to the literature by integrating return, trading activity, and volatility indicators within an event-study framework.